Effects of Four-Month Exercise Program on Correction of Body Posture of Persons with Different Visual Impairment - Damira Vranesic-Hadzimehmedovic; Izet Bajramovic; Slavenko Likic; Muhamed Tabakovic; Dzenana Imamovic (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2018)
The aim of this study was to determine the effect of a four-month specific exercise program on correcting the posture of persons with different visual impairment. The sample consisted of 20 elementary students with visual impairment diagnosis, 11 boys and 9 girls aged 9-14 (12±0.6). The classification of the examinees was performed according to the established degree of visual impairment, 10 blind persons and 10 partially sighted persons. The pupils voluntarily participated in the exercise program. The exercise program was structured of two phases: exercise on dryland and exercise in water. A total of 36 exercise units were completed during four months period. Seven tests were used to evaluate the body posture, based on the determination of segmental dimensions and the visual projection of the marked points. The contents of the program were performed with the aim of preventing and correcting the observed irregularities of the body posture. The t-test scores indicated statistically significant differences between two measurements (p<0.05, p<0.01). It can be concluded that elementary movements, performed through dryland and especially water exercises, had a good effect on correcting the body's posture of blind and partially sighted persons.